Needlestick injury and psychomotor performance as measured by pursuit-aiming test in health-care professionals - Gholamreza Pouryaghoub; Akbar Azizi-Alvandi; Nazanin Izadi (Wolters Kluwer Medknow Publications, 2022)
Background: Several factors play a role in Needlestick Injury (NSI). We aimed to determine the association of NSI with psychomotor performance in health-care workers. Materials and Methods: In this cross-sectional study, demographic, occupational characteristics, and needlestick history were completed for 357 health personnel of a university hospital of Tehran in 2019 through a checklist. Psychomotor performance was measured using a pursuit-aiming test. Results: Most of the NSI occurred in nurses. The mean age of the workers with a positive history of NSI was significantly lower compared to their peers with a negative history, and similarly, they had lower work experience. After adjustment for the confounding variables, the correct pursuit-aiming test had a borderline association with the occurrence of the NSI. Conclusions: Psychomotor performance had a borderline association with the history of NSI.